Factores asociados a la elaboración de tesis en la Universidad Nacional de Asunción, Paraguay - Soto Figueredo, Carmiña Hilda (Universidad de Costa Rica, 2020)
Some results of the research contained in the author´s doctoral thesis are shown around the factors associated with the preparation of master´s and doctoral theses, where the selection of the content made for this article, was the aim was to analyze the factors associated with the elaboration of master and doctoral´s thesis from Universidad Nacional de Asunción, taking data from the 2004-2014. A quali-quantitative study was carry out, with analytical, retrospective and cross-sectional design, with a non-probabilistic sample of 189 research subjects. Significant association between part/full time workX2 (1, N=189)=5,934, p=0,018,scholarshipX2 (1, N=189)=12,45 p=0,0001, teaching and research activityX2 (4, N=189)=20,44, p=0,0001, meeting with the advisorX2 (3, N=189)=84,6, p=0,001 and make the thesis were found; and not significant association between sex, age to begin de postgraduate program, thesis committee o advisor, making curse or workshop about thesis, publication and to make de thesis was found. In both, as the main factor that prevents the realization of the thesis, was methodological question (22%), it does not how to do it, has problems with writing. The interviews showed the demotivation of students regarding the lack of agreement between evaluators, tutors and jury. It was possible to visualize the complex and multifactorial character that leads to a non-thesis situation.